Capitalism in Slavery, Slavery in Capitalism: Original Accumulation, Slave Rent, and the Formation of the World Market - Tomich, Dale W. (Comparativ, 2021)
This chapter examines the relation of capitalism and slavery by reinterpreting the role of slavery in the formation of the capitalist world-economy beginning in the sixteenth century. By distinguishing between Marx’s theory of capital and the history of capitalist development, it construes historical capitalism as a global system embracing multiple forms of social labour. Atlantic slavery, it argues, is a specific form of commodity production that is integral to historical capitalism from its inception. The article proceeds to explore the specific role of Atlantic slavery in the original accumulation of capital, that is, the formation of the system. Surplus production and appropriation were based on slave rent, that is on ownership of the slave as property, not on ownership of the land. This relation created a very mobile and dynamic form of labour organization that was suited to the open commodity frontiers of the tropical and subtropical Atlantic. The expansion of slave labour in the south Atlantic played a fundamental role in creating the world division of labour and world market of the sixteenth century.